An Investigation of the Risk Factors and Prevalence of Alzheimer's Disease in the Eastern Region of Turkey A Population Based Door-to-Door Survey. Issue 2 (April 2015) - Ertekin, Ayfer; Demir, Recep; Özdemir, Gökhan; Özel, Lütfi; Özyıldırım, Ercan; Ulvi, Hızır
No abstract available